Two new uncommon 3D cobalt-based metal organic frameworks: Temperature induced syntheses and enhanced photocatalytic properties against aromatic dyes. (March 2021) - Wang, Jun; Zhou, Shanhe; Chen, Chen; Lu, Lu; Li, Baohong; Hu, Wuxin; Kumar, Abhinav; Muddassir, Mohd.
Abstract: The reaction of 5-fluorine-3-(3, 5-dicarboxylphenxoy)benzoic acid (H3 L) with cobalt(II) salt in presence of 1, 1'-(1, 4-butanediyl) bis (imidazole) (bib) linker yielded two new metal–organic frameworks (MOFs) with compositions [Co4 ( μ 3 -OH)2 (H2 O)2 (L)2 (bib)1.5 (CH3 CN)·3H2 O · CH3 CN] (1) and [Co8 ( μ 3 -OH)4 (L)4 (bib)4 ·8CH3 CN] (2) . The single crystal X-ray diffraction revealed that 1 exhibited an unusual 3D 3, 8-connected framework with 3, 8T25 topology based on [Co4 (μ3 -OH)2 ] tetranuclear cobalt clusters as secondary building units (SBU) with a (4 3 ) (4 12 ·5 4 ·6 4 ·8 8 ) Schläfli symbol. In 2, by substituting the CH3 CN with neutral N-ligand, a 3D 3, 8-connected MOF with 3, 10T9 topology and a point symbol of {4 18 .6 24 .8 3 }.{4 3 }2 has been obtained. This represents a highly connected uninodal network topology presently known for flexible carboxylate-based MOF systems. Both the MOFs have been used as photocatalysts for photodegradation of a model organic dye methyl violet (MV). The photocatalytic experiments demonstrated that both 1 and 2 displayed efficient photocatalytic performances to degrade MV under UV irradiation. The plausible mechanism through which both the MOFs displayed photocatalytic properties have been proposed by using band gap calculations. Graphical abstract: Two cobalt based MOFs synthesized and influence of temperature on architectures of MOFs, band gap and photocatalytic properties studied. Image 1 Highlights: Two Co(II)-based MOFs synthesized by variation in temperature. The observed difference in topologies and band gaps in both MOFs attributed to effect of temperature. Both MOFs used as photocatalyst for the photodegradation of aromatic dye methyl violet. The plausible photocatalytic mechanism was addressed by using band gap calculations.